Address by Mr Koïchiro Matsuura, Director-General of UNESCO, on the occasion of the Forum: Sustainable Development of the Arctic Countries and the Northern Regions of the Russian Federation in the Context of Education, Science and Culture; Yakutsk, Republic of Sakha (Yakutia), Russia, 24 July 2006 - UNESCO. Director-General, 1999-2009 (Matsuura, K.) (24 July 2006, 2006)
Electronic version only